(untitled) (Journal of Governance and Development (JGD), 2024)
The social policy that the government in Malaysia implemented had positive influences on the local community and economy in Malaysia as well, which focused on the Consumer Price Index (CPI) and the idea that the trend would change if social policy were made. A study focused on the effect of social policy specified in Malaysia’s education, health, and housing areas on CPI. This study used the quantitative method based on the model of ordinary least squares (OLS), and CPI (Y) was the dependent variable, while government education spending (X1), government health spending (X2), and government housing spending (X3) were the independent variables. According to the results of this research, it seems that there was a positive impact of social policy on the CPI, but no significant social policy that the Malaysian government implemented had a determined power over the CPI. Most country research on the impact of social policy on CPI was also insignificant, based on the previous studies. These findings found that CPI was affected by other factors apart from social policy as well and need to be studied as potential factors in the future, as there was a slight significance. To emphasize this study, ARMA is the best-suggested way to analyse the trend of CPI in Malaysia.